2022
DOI: 10.1111/bph.15757
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological metabolic changes associated with disease modify the proarrhythmic risk profile of drugs with potential to prolong repolarisation

Abstract: Background and Purpose Hydroxychloroquine, chloroquine and azithromycin are three drugs that were proposed to treat coronavirus disease 2019 (COVID‐19). While concern already existed around their proarrhythmic potential, there are little data regarding how altered physiological states encountered in patients such as febrile state, electrolyte imbalances or acidosis might change their risk profiles. Experimental Approach Potency of human ether‐à‐go‐go related gene (hERG) block was measured using high‐throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…In contrast, for moxifloxacin, no significant change in potency was observed between physiological temperature and 42 °C (Alexandrou et al 2006 ). Similarly, our investigations showed that febrile temperature significantly increased the potency of azithromycin as compared to physiological temperatures, while for chloroquine and hydroxychloroquine, potency was significantly reduced (TeBay et al 2021 ). Further insights into the effect of temperature on hERG block can be gleaned from experiments performed at subfebrile temperatures, which are far more common in the literature.…”
Section: Temperaturesupporting
confidence: 53%
See 4 more Smart Citations
“…In contrast, for moxifloxacin, no significant change in potency was observed between physiological temperature and 42 °C (Alexandrou et al 2006 ). Similarly, our investigations showed that febrile temperature significantly increased the potency of azithromycin as compared to physiological temperatures, while for chloroquine and hydroxychloroquine, potency was significantly reduced (TeBay et al 2021 ). Further insights into the effect of temperature on hERG block can be gleaned from experiments performed at subfebrile temperatures, which are far more common in the literature.…”
Section: Temperaturesupporting
confidence: 53%
“…The authors also demonstrated that block by N-methyl-verapamil, a permanently charged analogue of verapamil, was not sensitive to changes in pH, confirming that the effect on block was specifically due to the charge on the drug molecule (Zhang et al 1999 ). Similar explanations have also been posed for other drugs such as flecainide (Du et al 2011 ), ibogaine (Thurner et al 2014 ), fentanyl (Tschirhart and Zhang 2020 ) and hydroxychloroquine (TeBay et al 2021 ) supporting the case that this is a common mechanism for the effect of pH on a drug’s potency to bock ERG.…”
Section: Acidosis and Alkalosismentioning
confidence: 61%
See 3 more Smart Citations